"Never the first time on a patient": the stakes of high-fidelity simulation for safety training. Issue 5 (25th October 2018) - Cuvelier, Lucie
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: An operative approach is described that is designed to structure the debriefing along three axes. Practical implications: The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.